2016
DOI: 10.1016/j.critrevonc.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mucosal toxicity of concomitant chemo-radiotherapy in patients with locally-advanced squamous cell carcinoma of the head-and-neck in the light of a novel mathematical model

Abstract: Background: In the last several decades, combined radiotherapy (RT) and chemotherapy (CT) have beenrecognized as feasible in locally-advanced-squamous-cell-carcinoma of the head-and-neck (LA-HNSCC).Several meta-analyses identified concurrent RT + CT (CRT) most likely effective approach respect toRT-alone. However, radiobiological models comparing different chemotherapeutic schedules againstdelivered RT fractionation schedule for overall survival and toxicity are still needed.Methods and materials: Based on 9 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Overall, 12.8% of severe toxicities were registered, a value markedly lower than previously published data regarding the safety of 5-FU-based therapy with or without radiotherapy in head-and-neck cancer, i.e. 25%–50%, including frequent cases of febrile neutropenia [1214]. Of note, it is not possible to attribute the 12.8% remaining toxic events to a specific drug, including 5-FU, because patients were all treated with multiple therapies associating mostly platinum derivatives, or paclitaxel, with possible combined effects in terms of cumulative toxicities.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, 12.8% of severe toxicities were registered, a value markedly lower than previously published data regarding the safety of 5-FU-based therapy with or without radiotherapy in head-and-neck cancer, i.e. 25%–50%, including frequent cases of febrile neutropenia [1214]. Of note, it is not possible to attribute the 12.8% remaining toxic events to a specific drug, including 5-FU, because patients were all treated with multiple therapies associating mostly platinum derivatives, or paclitaxel, with possible combined effects in terms of cumulative toxicities.…”
Section: Discussionmentioning
confidence: 62%
“…However, 31% to 34% of treated patients have doselimiting toxicities (Meta-Analysis Group . Concomitant administration of 5-FU and RT increases the rate of observed grade 3 or higher acute mucositis (Strigari et al, 2016). Bazan et al (2013) reported that acute hematologic toxicity in patients treated with pelvic RT concomitant with 5-FU was 8% higher than in those undergoing RT alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of 2D radiotherapy and early 3D conformal radiotherapy, potential for sparing of the oral cavity was limited. Models derived from trials conducted in this era show clear relationships between prescription dose converted to biologically effective dose (BED) or an equivalent dose in 2 Gray (Gy) fractions (EQD 2 ) and the rate of grade 3 mucositis [ 23 , 24 ]. Attempts have also been made to model the additional effect on oral mucositis of synchronous chemotherapy [ 25 , 26 ].…”
Section: Oral Cavity Oar Definitionmentioning
confidence: 99%
“…Such systems have the advantage of being simple to use. In addition, early radiobiological models linking mucositis and prescription dose were based on such physician scored objective systems [ 23 , 24 ]. More complex systems for scoring mucositis such as the Oral Mucositis Assessment Scale (OMAS) where the extent of mucositis is incorporated by assigning a grade to different anatomical regions within the mouth have subsequently been developed [ 37 ].…”
Section: Measurement Of the Acute Mucosal Reactionmentioning
confidence: 99%